2021
DOI: 10.1161/strokeaha.120.031599
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy Versus Combined Thrombolysis and Thrombectomy in Patients With Acute Stroke

Abstract: Background and Purpose: A recent randomized controlled trial DIRECT-MT (Direct Intra-Arterial Thrombectomy to Revascularize AIS Patients With Large Vessel Occlusion Efficiently in Chinese Tertiary Hospitals) compared the safety and efficacy of mechanical thrombectomy (MT) versus combined intravenous thrombolysis (IVT) and MT for acute large vessel occlusion. The current study utilized a prospective, nationwide registry to validate the results of the DIRECT-MT trial in a real-world practice setting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…In terms of safety, we found bridging MT increased the incidence of PH-2 and showed a trend toward a higher incidence of sICH (10.06% vs 5.67%, respectively; adjusted P=0.061). The SKIP trial and two multicenter retrospective studies also showed that bridging thrombectomy had a higher risk of ICH, 11,14,19 which support our result to a certain extent. This suggests that IVT increases the risk of ICH in elderly patients.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In terms of safety, we found bridging MT increased the incidence of PH-2 and showed a trend toward a higher incidence of sICH (10.06% vs 5.67%, respectively; adjusted P=0.061). The SKIP trial and two multicenter retrospective studies also showed that bridging thrombectomy had a higher risk of ICH, 11,14,19 which support our result to a certain extent. This suggests that IVT increases the risk of ICH in elderly patients.…”
Section: Discussionsupporting
confidence: 88%
“…The ANGEL-ACT is a nationwide, multicenter, prospective registry program for patients who undergo endovascular treatment for acute LVO from 111 stroke centers in China. 11 This research program was approved by the ethics committee of the Second Affiliated Hospital of Xi’an Jiaotong University and each participating site. Each participant or his/her representative gave written informed consent before being enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Univariable comparisons of baseline characteristics between patients with and without AF were performed using Mann-Whitney or Pearson’s chi-square tests. To improve the comparability between the two groups, a 1:1 propensity score matching (PSM) was performed by using a caliper distance of 0.05 [ 25 ]. For comparing the outcomes between both groups, the odds ratios (OR) or common OR with their 95% confidence intervals (CI) were calculated using a binary or ordinal logistic regression model, if applicable.…”
Section: Methodsmentioning
confidence: 99%
“…We deemed nine of the 73 reviewed studies to be eligible. Three RCTs (DIRECT-MT, DEVT and SKIP [20][21][22] ) and six observational studies [23][24][25][26][27][28] were included after the full texts of the studies were screened. In all nine studies, patients with AIS-LVO who were eligible to undergo both IVT and EVT were assigned to undergo direct EVT or to undergo a combined treatment with intravenous alteplase before EVT.…”
Section: Study Characteristicsmentioning
confidence: 99%